1985
DOI: 10.1152/jn.1985.54.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Inferior olivary neurons in the awake cat: detection of contact and passive body displacement

Abstract: We have recorded from 306 neurons in the inferior olive of six alert cats. Most of the cats were trained to perform a simple task with the forelimb. We observed the neural responses to a wide variety of cutaneous and proprioceptive stimuli, as well as responses during spontaneous and learned active movements. Neurons responsive to somatosensory stimulation were found in all parts of the inferior olive, and they were roughly evenly divided between those responsive to cutaneous stimulation and those responsive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
155
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(173 citation statements)
references
References 0 publications
17
155
1
Order By: Relevance
“…The response of the inferior olive to deviant stimuli shown in the present study is consistent with early electrophysiological studies demonstrating that the olivary neurons are highly sensitive to unexpected external sensory stimuli (22,(34)(35)(36)(37). This finding was interpreted from the perspective of motor control to indicate that the inferior olive signals unexpected events and therefore errors or mismatches between intended and achieved movement (38-41).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The response of the inferior olive to deviant stimuli shown in the present study is consistent with early electrophysiological studies demonstrating that the olivary neurons are highly sensitive to unexpected external sensory stimuli (22,(34)(35)(36)(37). This finding was interpreted from the perspective of motor control to indicate that the inferior olive signals unexpected events and therefore errors or mismatches between intended and achieved movement (38-41).…”
Section: Discussionsupporting
confidence: 92%
“…The results were consistent with the enhanced response of the inferior olive and climbing fiber system to unexpected sensory input consistently shown in electrophysiological studies, and further indicated that the inferior olive response to unexpected stimuli is specific to timing (22,23). In the present study, we used a similar eventrelated fMRI paradigm to determine the effect of the subject's awareness on the transient neural responses of the inferior olive and cerebellar cortex to changes in stimulus timing.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Since the cerebellum is more active during error corrections, it is likely that climbing fibers are signaling movement error, leading to LTD of Purkinje cell-parallel fiber synapses (Gellman et a!., 1985;Ito, 1991;Ito & Karachot, 1992;Oscarsson, 1969;Simpson eta!., 1996).…”
Section: Evidence For a Cerebellar Role In Handwritingmentioning
confidence: 99%